45th Winter School on Wave and Quantum Acoustics and XLIVth Winter School on Environmental Acoustics and Vibroacoustics - XLIVth Winter School on EA&V, 45th Winter School on WQA; (Archives of Acoustics, 2016)
On behalf of Upper Silesian Division of the Polish Acoustical Society (main organizer) and Committee of Acoustics of the Polish Academy of Sciences (co-organizer) we are pleased to announce that it is nearing the end of preparations for the conduct traditionally organized Conferences, which will take place as previously in Szczyrk. At the moment, more than 50 people have confirmed participation in Conferences. They will present more than 40 lectures and reports.45th Winter School on Wave and Quantum Acoustics constitutes a platform for sharing the results and achievements obtained in different branches of physical acoustics (e.g. molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state etc.). Moreover, researches in some selected topics related to those mentioned above (e.g. optoelectronics, relaxation processes) will also be presented during the school. Currently, during the Conference Workshop on Acoustoelectronics and Workshop on Molecular Acoustics, Relaxation and Calorimetric Methods will be held – however, there is a possibility of organizing workshops on other subjects in the future. We would like to invite scientific centers and groups to cooperate in organizing workshops on the subjects of their interests.XLIVth Winter School on Environmental Acoustics and Vibroacoustics is the forum for all environmental and vibroacoustics fields. Particularly it concerns traffic noise, vibroacoustics of machines, room acoustics, building acoustics, noise protection and similar problems.